Pendampingan Kegiatan Keagamaan Ramadhan dalam Rangka Pembentukan Karakter Siswa SD Inpres Kampus Unhas - Darmayanti, Dyan Paramitha; Manda, Darman; Arifin, Iqbal; Syukur, Muhammad; Sulmiah, Sulmiah (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity was carried out on March 26 to 28, 2024, to assist in implementing the Ramadan religious program at SD Inpres Kampus Unhas. This program is part of Campus Teaching Batch 7 and aims to instill Islamic values and strengthen student character education through educational and fun activities. The activity was attended by 55  students, 10 teachers, 5 Teaching Campus students, and a supervisor. The method used is a participatory-collaborative approach, which includes the initial observation stage, planning with the school, implementing core activities, and evaluating the results of assistance. The main activities included Flash Islamic Boarding School, Ramadan Amaliah Competition (adhan, hifzhil Qur'an, and lecture), and Iftar. All activities are designed to actively involve students and build a religious and meaningful Ramadan atmosphere. The mentoring results showed an increase in student participation and enthusiasm in religious activities, the growth of self-confidence, and the creation of positive relationships between students, teachers, and lecturers. Teachers responded enthusiastically and appreciated the contribution of students and lecturers in strengthening students' character. This activity is considered successful and can be used as a model for implementing religious programs in other elementary schools..